The Self-Absorption Effect of Ni-63 Beta Source to the Silicon Carbide based Betavoltaic Battery - Rahastama, Swastya; Saputra, Yohannes Dwi; Waris, Abdul (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2020)
A typical planar structure is the most feasible conceptual design of betavoltaic battery due to its simplicity. The self-absorption of beta source, however, causes a limitation to the geometrical efficiency.Â Herein, we tried to investigate the self-absorption event in Ni-63 beta source by changing the geometrical aspects and evaluated its effect on each layer of a 4H-SiC semiconductor as the radiation-electricity converter. The design configuration from previous literature was adopted and the model was developed using Monte Carlo N-Particle X (MCNPX) consists of radioisotope source, semiconductor, and also ohmic contacts. The energy of beta emission was adjusted to the actual Ni-63 beta spectra with an isotropic distribution of ejected particles. The average beta energy deposition degrades along with the addition of source mass thickness, but the n+ substrate has a unique result where a peak is observed at 0.1246 mg/cm2 due to the self-absorption effect. Furthermore, the rectangular surface area magnification gives a positive impact on the beta energy deposition up to 2.48% and the photon average energy deposition up to 137.21%. Â The results of average electron absorbed dose are consistent with Oldano-Pasquarelli semi-empirical theory of self-absorption in the beta source, where the upper layer receives a wider angular distribution of particles compared to the lower one, which corresponds to the counting geometrical coefficients.